ChemInform Abstract: Nickel‐Catalyzed Asymmetric Ring Opening of Oxabenzonorbornadienes with Arylboronic Acids. Issue 47 (6th November 2014) - Zeng, Zhongyi; Yang, Dingqiao; Long, Yuhua; Pan, Xuejing; Huang, Guobao; Zuo, Xiongjun; Zhou, Wen
Abstract In comparison to related transition metal‐catalyzed protocols, this procedure is characterized by utilization of a cheaper catalyst precursor, low catalyst loading, higher efficiency, enantioselectivity, and functional group tolerance.